DEVELOPMENT OF MADURA LANGUAGE LEARNING MEDIA JUNIOR HIGH SCHOOL LEVELS IN PAMEKASAN - M., Khoiri; Kusyairi, Kusyairi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
The aims of this research are to: (1) develop instructional video media for appropriate Madurese language subjects at the junior high school level. (2) determine the quality of learning video media for Madurese language subjects that are appropriate at the junior high school level. The design of this research is research and development (research & development). This development research is a development with 3 steps, namely: (1) planning: determining needs and objectives, collecting sources, and generating ideas. (2) design: making flowcharts, making storyboards, and preparing scripts. (3) development: producing video and audio, programming materials, preparing supporting components, evaluating and revising. The results of the evaluation of the learning media that have been made are (1) based on student responses about the Madurese language learning video media used in schools which are in the medium criteria category, can be used but need minor revisions, namely 72.58 according to the percentage of criteria. (2) Based on the results of expert validation about the Madurese language learning video media used in schools, it is in the category of low criteria and can be used but needs revision, which is 70.00 according to the percentage of criteria.